Preparing Students for Mathematics Lessons and Checking Their Knowledge of Mathematics (Global Scientific Review, 2022)
This article describes in detail the preparation of students for mathematics lessons and the examination of their knowledge of mathematics, the analytical and logical thinking ability of a student who has mastered mathematics well, and the examination of students' level of mastery in various ways